KAJIAN POLA OPERASI WADUK KEUREUTO UNTUK MEMENUHI KEBUTUHAN AIR BAKU DI KABUPATEN ACEH UTARA PROVINSI ACEH - Ramadhan, Kadri; Masimin, Masimin; Syamsidik, Syamsidik (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2018)
Abstract: One of the rivers that has potency to be developed for the purpose of fulfilling the need of water in North Aceh Regency is Krueng Keureuto River. From its potential characteristic, the appropriate conservation effort is by constructing a water reservoir. The construction of Keureuto Reservoir is located in Krueng Keureutos stream in Paya Bakong Sub-district. The purpose of this research is to determine inflow debit of Keureuto Reservoir based on the probability of debit by dividing it into three operation year, to determine the debit of water need of Keureuto Reservoir for the need of raw water, and to determine optimization to optimize the Elevation of water surface in Keureuto Reservoir in wet year, normal year, and dry year. The method of reservoir operation was analyzed by using optimization technique by using program solver (Microsoft Excel). The first step is done by dividing the inflow debit data into three kinds of operation year, that is, dry, normal, and wet year. Next, the need of water in Keureuto Reservoir was analyzed based on the need of water. Storage is obtained from curve data of reservoirs capacity while output was obtained from the data of reservoirs need of water. Then, the arrangement and optimization in operation pattern of Keureuto Reservoir was done. The water of Keureuto Reservoir is used to fulfil three necessities, that is, to fulfill the preservation of the river stream as much as 1,11m3/s, to fulfil the peoples water necessity as much as 0,50 m3/s and to fulfil the need of water for irrigation as much as 0,82 m3/s. The result of optimization of fulfilling the need of raw water from Keureuto Reservoir shows that the maximum elevation in dry year is 98,75m and the minimum elevation is 80 m. In normal year, the maximum elevation is 100 m and the minimum is 81 m, while in wet year, the maximum elevation is 100,60 m and the minimum is 83 m.Abstrak: Salah satu sungai yang berpotensi untuk dikembangkan dalam upaya pemenuhan kebutuhan air di wilayah Kabupaten Aceh Utara adalah Sungai Krueng Keureuto, Dari potensi air tersebut maka upaya konservasi yang tepat adalah dengan membangunan sebuah waduk. Pembangunan Waduk Keureuto ini berada pada aliran Sungai Krueng Keureuto Kecamatan Paya Bakong. Maksud dari kajian ini adalah Menentukan debit inflow Waduk Keureutoe berdasarkan probabilitas debit dengan pembagian tiga jenis tahun operasi, Menentukan debit kebutuhan air Waduk Keureuto untuk kebutuhan air baku, dan Melakukan optimasi untuk mengoptimalkan Elevasi Muka Air Waduk Keureuto pada Tahun Basah, Tahun Normal dan Tahun Kering. Metode pengoperasian waduk dianalisis menggunakan teknik optimasi dengan program solver (Microsoft Excel). Tahapan yang dilakukan adalah data debit inflow waduk dibagi menjadi tiga jenis tahun operasi yaitu tahun kering, normal, dan tahun basah. Selanjutnya dianalisis kebutuhan air waduk Keureuto berdasarkan data kebutuhan air. Storage diperoleh dari data lengkung kapasitas waduk, sedangkan output diperoleh dari data kebutuhan air waduk. Setelah itu penyusunan dan optimasi pada pola operasi Waduk Keureuto. Air waduk Keureuto digunakan untuk memenuhi tiga kebutuhan yaitu pemenuhan kebutuhan aliran pemeliharaan sungai sebesar 1,11 m3/s, pemenuhan kebutuhan air penduduk sebesar 0,50 m3/s serta pemenuhan kebutuhan air untuk irigasi sebesar 0,82 m3/s. Hasil optimasi untuk pemenuhan kebutuhan air baku dari Waduk Keureuto menunjukkan bahwa Elevasi Maksimum pada tahun kering berada pada Elevasi 98,75 m, dan Elevasi Minimum berada pada Elevasi 80 m, untuk tahun normal Elevasi Maksimum berada pada Elevasi 100 m dan Elevasi Minimum berada pada Elevasi 81 m, sedangkan Elevasi Maksimum tahun basah berada pada Elevasi 100,60 m dan Elevasi Minimum berada pada Elevasi 83 m.